Thermal Safety of Endoscopic Usage in Robot-Assisted Middle Ear Surgery: An Experimental Study - Pan, Jinxi; Tan, Haoyue; Shi, Jun; Wang, Zhaoyan; Sterkers, Olivier; Jia, Huan; Wu, Hao (Frontiers in Surgery, 2021)
Objectives: The widespread application of endoscopic ear surgery (EES), performed through the external auditory canal, has revealed the limitations of the one-handed technique. The RobOtol® (Collin ORL, Bagneux, France) otological robotic system has been introduced to enable two-handed procedures; however, the thermal properties of dedicated endoscopes, which are usually used in neurosurgery, called “neuro-endoscopes”, have not yet been clarified for the robotic systems. In this study, we aimed to profile the thermal characteristics of two dedicated neuro-endoscopes, as compared to endoscopes used routinely in manual EES, called “oto-endoscopes”, and defined by a smaller diameter and shorter length, and to discuss the safe application of robotic assistance in EES. Methods: Two neuro-endoscopes (3.3 mm, 25 cm, 0°/30°) were studied using two routine light sources (LED/xenon), and two routine oto-endoscopes (3 mm, 14 cm, 0°/30°) were initially measured to provide a comprehensive comparison. Light intensities and temperatures were measured at different power settings. The thermal distributions were measured in an open environment and a human temporal bone model of EES. The cooling measures were also studied. Results: Light intensity was correlated with stabilized tip temperatures (P<.01, R2=0.8719). Under 100% xenon power, the stabilized temperatures at the tips of 0°, 30° neuro-endoscopes, and 0°, 30° oto-endoscopes were 96.1°C, 60.1°C, 67.8°C, and 56.4°C, respectively. With 100% LED power, the temperatures decreased by about 10°C, respectively. For the 0° neuro-endoscope, the illuminated area far away 1cm from the tip was below 37°C when using more than 50% both power, while this distance for 30° neuro-endoscope was 0.5cm. In the EES temporal bone model, the round window area could reach 59.3℃ with the 0° neuro-endoscope under 100% xenon power. Suction resulted in a ~1-2℃ temperature drop, while a 10mL saline rinse gave a baseline temperature which lasted for 2.5 minutes. Conclusion: Neuro-endoscope causes higher thermal releasing in the surgical cavity of ESS, which should be especially cautious in the robotic system usage. Applying submaximal light intensity, a LED source and intermittent rinsing should be considered for the safer robot-assisted EES using a neuro-endoscope that allows a two-handed surgical procedure.